Processos subjetivos na superação das dificuldades de aprendizagem de biologia - BEZERRA, Hanna Patricia da Silva (Universidade Federal do Pará, 2023)
This paper presents the results of an investigation into overcoming learning difficulties in Biology, based on González Rey's Theory of Subjectivity, in a cultural-historical perspective. We aimed to understand the subjective and operational dimensions of learning difficulties in Biology, as well as the processes of change in the subjective configuration of the action of learning Biology that favor overcoming the learning difficulties of the curricular component. The research methodology was based on Qualitative Epistemology and the ConstructiveInterpretative Method. The research participants were three students, identified with Biology learning difficulties and who were attending high school. We carried out a field research, in which we used, for the construction of information, self-assessment, sentence complements, conversational dynamics, informal conversations, observations and document analysis. Educational practices were also carried out with the participants in the form of workshops, aiming to contribute to overcoming learning difficulties, through strategies that recognized their uniqueness, encouraging autonomy and protagonist, the explicitness and contrast of models and the hierarchical integration of the students' implicit theory to the scientific knowledge of Biology. We constructed three case studies and, based on the interpreted information, elaborated a theoretical production on the operational dimension of learning difficulties in Biology, highlighting the epistemological, ontological and conceptual incompatibilities between the learners' implicit theories and the scientific theory, reverberating, mainly , in problems to contextualize and generalize the contents and understand them in a systemic perspective. From the study of the subjective configuration of the participants' action of learning Biology, we developed theoretical reflections about the subjective dimension of their learning difficulties, considering: 1) The learning difficulties constituted by the mobilization of subjective meanings arising from the history of school life, which made the production of operational and subjective resources to learn Biology unfeasible; 2) Learning difficulties constituted by the denial of the expression of the condition of agent or subject and of comprehensive and/or creative learning. In the three cases, we interpreted changes in the subjective configuration of the action of learning Biology, in view of the production and/or mobilization of subjective meanings that favor learning. From this perspective, the results substantiate the thesis that learning difficulties in learning Biology result from the production of meanings that are unfavorable to learning or to the development of relational and operational resources that make it possible. Overcoming such difficulties demands processes of change and/or subjective development, in view of the mobilization and/or reciprocal production of operational, relational and subjective resources, which favor the learning of the contents of this curricular component